Cyclophilin A in Ruptured Intracranial Aneurysm. Issue 39 (September 2015) - Kao, Hung-Wen; Lee, Kwo-Whei; Chen, Wei-Liang; Kuo, Chen-Ling; Huang, Ching-Shan; Tseng, Wan-Min; Liu, Chin-San; Lin, Ching-Po; Yong., Li
<x xml:space="preserve">Abstract</x> Abstract Cyclophilin A (CyPA), an oxidative stress-induced factor, was found to play an important role in the aneurysm formation. Our working hypothesis was that the plasma level of CyPA in ruptured intracranial aneurysm could predict the neurological outcome. From 2011 to 2013, a total of 36 patients with ruptured saccular intracranial aneurysm were recruited in our study. Before coil embolization, we draw blood samples at the orifice of a culprit aneurysm and in the remote peripheral vein for measurements of the CyPA levels. We utilized the modified Rankin scale 30 days after aneurysm rupture as the outcome measure. Generalized linear models were used to estimate the adjusted odds ratios of the poor neurological outcome given the presence of high plasma level of CyPA. The aneurysmal and venous CyPA levels were significantly associated with the initial clinical severity (P = 0.004 and 0.03, respectively) and 30-day outcome (P = 0.01 and 0.02, respectively). The aneurysmal CyPA levels modestly correlated with age and high Fisher grade (ρ = 0.39 and 0.41; P = 0.02 and 0.01, respectively). The aneurysmal CyPA levels strongly correlated with the venous counterpart (ρ = 0.89; P < 0.001). Patients with high levels of aneurysmal CyPA were 15.66 times (95% CI, 1.48–166.24; P = 0.02) more likely to have worse neurological outcome than those with the low levels after adjustment of the age, gender, and the documented confounding factors. High plasma level of CyPA is a significant prognostic biomarker for poor neurological outcome in patients with ruptured intracranial aneurysm.